Koncepcja interesu grupy spółek oraz jej zastosowanie w polskim porządku prawnym na przykładzie ochrony wspólników mniejszościowych spółki zależnej - Buszkiewicz, Mateusz (My University, 2025)
Rozprawa doktorska analizuje ochronę wspólników mniejszościowych spółki zależnej w kontekście polskiej regulacji grup spółek opartej na koncepcji ich interesu. Autor bada nowe środki ochrony wynikające z nowelizacji KSH oraz ich wpływ na dotychczasowe mechanizmy. Główna teza wskazuje, że obecne regulacje nie zapewniają wystarczającej ochrony wspólników mniejszościowych. Praca obejmuje analizę rozwoju prawa grup spółek w UE i w Polsce, a także porównanie różnych modeli prawnych, w tym inspiracji rozwiązaniami francuskimi. Autor omawia strukturalne cechy grup spółek, ich powstawanie oraz kluczowe założenia przyjętego modelu. Szczegółowo analizuje wpływ koncepcji interesu grupy na ochronę praw majątkowych i korporacyjnych wspólników mniejszościowych oraz możliwość ich wystąpienia ze spółki. Rozprawa ocenia skuteczność wprowadzonych regulacji i wskazuje na ich potencjalne niedoskonałości. The dissertation analyzes the protection of minority shareholders of a subsidiary in the context of Polish regulation of groups of companies based on the concept of their interest. The author examines the new protection measures resulting from the amendments to the CCC and their impact on the existing mechanisms. The main thesis indicates that the current regulations do not provide sufficient protection for minority shareholders. The work includes an analysis of the development of the law of groups of companies in the EU and Poland, as well as a comparison of different legal models, including inspiration from French solutions. The author discusses the structural features of company groups, their formation and the key assumptions of the adopted model. He analyzes in detail the impact of the group interest concept on the protection of property and corporate rights of minority shareholders and the possibility of their withdrawal from the company. The dissertation evaluates the effectiveness of the introduced regulations and points out their potential imperfections.
The concept of the interest of a group of companies and its application in the Polish legal system on the example of protection of minority shareholders of a subsidiary
Wydział Prawa i Administracji
Keywords: grupa spółek; koncepcja interesu grupy spółek; interes spółki; ochrona wspólników mniejszościowych; group of companies; concept of interest of a group of companies; interest of the company; protection of minority shareholders